Estudo da saúde de adolescentes usuários do CAPSi: níveis de estresse, sintomatologia psiquiátrica e violência - Lima, Letícia Saldanha de (2012)
Data presented by the World Health Organization where about 20% of the children and adolescents present some health problem, such occurrence might cause negative consequence in a short or long term in the development of youngsters (WHO, 2003). And coupled this information, different forms of violence are growing in an effective and comprehensive (LUMA, FERREIRA, VIEIRA, 2010). From these two perspectives, the following study aimed to investigate the occurrence levels of psychiatric symptoms and stress levels and violence among adolescent users of CAPS in Santa Maria.The sample consisted of a total of 52 adolescents. It was conducted a cross-sectional, descriptive, correlational with a quantitative and qualitative approach. The instruments used were a demographic data form and the Self-Report Questionnaire- SRQ-20 (MARY E WILLIAMs, 1986), Adolescents Stress Scale (ASS) (LUCARELLI, LIPP, 2005), Child Stress Scale (CSS) (TRICOLLI, LIPP, 2006), and a verbal check of violence throughout the development, conducted by the research group. The results were obtained through statistical descriptive analysis, inferential and Person correlational, through the statistical Pack SPSS 19.0. The sample comprised 32 (64%) boys and 18 (36%) girls, with a mean age of 14 years old. Among the key findings, it was observed that all adolescents from 12 to 14 years presenting some level of stress reaction. As for the item psychiatric symptoms, it was observed that the girls were represented with 80% of symptoms. Moderate correlation was found positive and statistically significant in the item symptom of psychological stress and psychiatric symptoms (r2 = 0.57, p = 0.001). From these data, it reinforces the need for a deeper investigation of the symptoms CAPSi symptomatology in adolescents with a view to promoting the health of this population.